2016
DOI: 10.1371/journal.pone.0163845
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Protective Responses upon Activation of L-Type Voltage Gated Calcium Channel in Macrophages during Mycobacterium bovis BCG Infection

Abstract: The prevalence of Mycobacterium tuberculosis (M. tb) strains eliciting drug resistance has necessitated the need for understanding the complexities of host pathogen interactions. The regulation of calcium homeostasis by Voltage Gated Calcium Channel (VGCCs) upon M. tb infection has recently assumed importance in this area. We previously showed a suppressor role of VGCC during M. tb infections and recently reported the mechanisms of its regulation by M. tb. Here in this report, we further characterize the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…It has been reported that an increase in calcium ion concentration inside Mfs increases phagosome-lysosome fusion and that mycobacteria depletes Ca 2+ concentration in Mfs to prevent this fusion [17]. We have also recently demonstrated the role of voltage-gated calcium channel regulated calcium influx in regulating phagolysosome fusion [11]. As shown in Fig.…”
Section: Rv3529c Aids Inhibition Of Phagosome-lysosome Fusion By M Bmentioning
confidence: 67%
See 2 more Smart Citations
“…It has been reported that an increase in calcium ion concentration inside Mfs increases phagosome-lysosome fusion and that mycobacteria depletes Ca 2+ concentration in Mfs to prevent this fusion [17]. We have also recently demonstrated the role of voltage-gated calcium channel regulated calcium influx in regulating phagolysosome fusion [11]. As shown in Fig.…”
Section: Rv3529c Aids Inhibition Of Phagosome-lysosome Fusion By M Bmentioning
confidence: 67%
“…To that end, cells were incubated with biopharmacologic inhibitors that prevent calcium release from intracellular stores or calcium influx from an external medium and inhibitors to PKC and ERK-MAPK, followed by stimulation with Pam 3 Csk 4 , in the presence or absence of Rv3529c. Recent reports from our laboratory have identified significant roles for these signaling intermediates in modulating defense responses of Mfs in M. tuberculosis [9][10][11][12]. As shown in Fig.…”
Section: Inhibition Of Ros By Rv3529c Is Dependent On Route Of Calciumentioning
confidence: 90%
See 1 more Smart Citation
“…The fact that no significant change was observed for IFN-γ, and IL-6, indicates that MprA and MprA* may not regulate the responses mediated by these cytokines. Gupta et al,(Gupta et al, 2010) can prolong the survival of the pathogen in the macrophage (Malik et al, 2000;Sharma et al, 2016). It is known that MprA has a role in persistence of infection (Zahrt & Deretic, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…THP-1 cells were maintained in RPMI-1640 (P04-18047Pan Biotech,Germany) supplemented with 10% Fetal Bovine Serum (Gibco) in 5% CO 2 in humidified environment at 37°C. For all the experiments, THP-1 monocytes were differentiated into macrophages with 50ng/ml PMA (Phorbol 12-myristate 13-acetate) (Sigma) for 16 hours followed by 24 hours of incubation in complete medium Sharma et al, 2016). The optimum concentration of protein for maximum activity was standardized using titration assay for MprA and MprA* ( Supplementary Fig 2).The differentiated THP-1 cells were treated with 15 μ g/ml of MprA and MprA* in all the subsequent experiments unless otherwise mentioned.…”
Section: Cell Culture and Protein Stimulationmentioning
confidence: 99%